Optimalisasi Penerapan Prinsip Good Governance dalam Pengelolaan Akutansi Publik pada UMKM Batik di Kelurahan Bendogerit - Lailin, Ulva Roifatul; Maharani, Wydha Mustika (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2025)
This study aims to examine how the principles of good governance can be optimally implemented in the management of public accounting in the batik industry in Bendogerit Village. Using a descriptive qualitative approach, data was collected through in-depth interviews, direct observation, and documentation from batik business owners, village officials, and relevant stakeholders. Financial management practices, from production to marketing, were analyzed to identify the extent to which principles such as transparency, accountability, participation, efficiency and effectiveness have been applied. The results showed that most business actors still use manual records and have not implemented a conventional accounting system, so the application of Good Governance principles has not been running optimally. This research recommends an optimization strategy that includes training, counseling, and cross-sector collaboration between the village government, batik MSMEs, and universities to build a simple, participatory, and community-based public accounting system. The findings not only describe the current state of financial governance, but also provide practical solutions to strengthen the accountability and professionalism of MSMEs in the local creative industry.